Oral History Program Interview: Joyce Vernon Seabolt - Seabolt, Joyce Vernon
Seabolt, born in 1928 in Fort Gibson, Oklahoma, describes his Cherokee and Oklahoma roots. He comments farm life regarding religion, men's and women's work, and how the Dust Bowl victimized farmers both environmentally and economically. His account of the trip to California in 1937 includes being stopped by border guards, but his life is centered in the Imperial Valley. Seabolt discusses the meaning of the term "Okie" then and now. He describes de facto segregation in the fields and neighborhoods between whites, blacks, and Mexican-Americans. People were stigmatized for living in government camps and being on welfare.